Monitoring metabolic status : predicting decrements in physiological and cognitive performance (Online access: National Academy of Sciences National Academies Press., 2004)
The U.S. military's concerns about the individual combat service member's ability to avoid performance degradation, in conjunction with the need to maintain both mental and physical capabilities in highly stressful situations, have led to and interest in developing methods by which commanders can monitor the status of the combat service members in the field. This report examines appropriate biological markers, monitoring technologies currently available and in need of development, and appropriate algorithms to interpret the data obtained in order to provide information for command decisions relative to the physiological "readiness" of each combat service member. More specifically, this report also provides responses to questions posed by the military relative to monitoring the metabolic regulation during prolonged, exhaustive efforts, where nutrition/hydration and repair mechanisms may be mismatched to intakes and rest, or where specific metabolic derangements are present.